1996
DOI: 10.1203/00006450-199602000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Three Years of Treatment with Growth Hormone and of One Post-Treatment Year, in Children with Severe Growth Retardation of Intrauterine Onset

Abstract: Seventy-eight prepubertal, non-GH-deficient children aged 8.1 +/- 0.2 y, with very short stature (mean, -3.2 SD) of intrauterine onset, were treated for 3 y with GH [0.4 (dose D1) or 1.2 (dose D2) IU/kg/wk] and 66 were followed during a 4th y without GH therapy. A 2-y intermediary report had demonstrated a GH dose-dependent acceleration of growth. During the 3rd y on GH, patients D2 (1.2 IU/kg/wk) continued with the same dose, whereas patients D1 (0.4 IU/kg/wk) were randomized to either continue on D1 (group D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
36
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 15 publications
11
36
2
Order By: Relevance
“…In addition, they have lower levels of IGF-I and IGFBP-3 than children born AGA of normal height (24). In the present study, the children born SGA had a significant increase in linear growth during the 2 years of GH treatment, in agreement with previous studies (37,38) introduction of recombinant GH therapy, much effort has been made to predict the growth response to GH therapy and to identify short children who will respond to treatment (24,39,40). In our previous report (24), chronological age at the start of GH therapy (the younger the child, the better the growth response), the mother's height expressed as SDS (the taller the mother, the better the growth response) and the 24-h GH secretion rate (the lower the GH secretion rate, the better the growth response) were the strongest predictors.…”
supporting
confidence: 93%
“…In addition, they have lower levels of IGF-I and IGFBP-3 than children born AGA of normal height (24). In the present study, the children born SGA had a significant increase in linear growth during the 2 years of GH treatment, in agreement with previous studies (37,38) introduction of recombinant GH therapy, much effort has been made to predict the growth response to GH therapy and to identify short children who will respond to treatment (24,39,40). In our previous report (24), chronological age at the start of GH therapy (the younger the child, the better the growth response), the mother's height expressed as SDS (the taller the mother, the better the growth response) and the 24-h GH secretion rate (the lower the GH secretion rate, the better the growth response) were the strongest predictors.…”
supporting
confidence: 93%
“…In some previous short term studies and in the present study, bone maturation was accelerated compared to that in untreated short children born SGA and compared to healthy children, respectively (18,20,22). However, it was remarkable that during the 5-yr treatment period, bone maturation in the total group as well as in the children who remained prepubertal during the study period appeared to be independent of the given GH dose, whereas no progressive acceleration of bone maturation was found.…”
Section: Discussioncontrasting
confidence: 37%
“…The untreated children did not show any spontaneous catch-up growth, indicating that they are destined to remain short (18,20,21). For our long term study, a randomized controlled trial with an untreated group until adult height was reached was considered unethical by several ethics committees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epi-analysis and multivariate analysis of four randomized multicentre studies using continuous or discontinuous GH treatment in doses from 0.033 to 0.1 mg/kg per day over 6 years, resulting in a similar height gain in the low-dose groups (0.033 mg/kg per day continuously over 6 years, or an average 0.032 mg/kg per day on discontinuous treatment over 6 years) and a better height increment in the continuous high-dose (0.067 mg/kg per day) group (+2.7 SD vs. +2.0 SD in the low-dose group after 6 years), identified the overall average GH dose over 6 years as one of the prime predictors of growth response [4]. Other studies have also shown dose-dependent catch-up growth during short-term GH treatment [14, 15]. …”
Section: Gh Dosementioning
confidence: 99%